Hewan Intersisi di Pantai Takisung Kabupaten Tanah Laut - Nurul Himmah; Agustina Ambar Pertiwi (Wahana-Bio: Jurnal Biologi dan Pembelajarannya, 2019)
Intersection animals generally live on sandy shores or wet soil, living permanently by sticking, hiding away, and burrowing at the bottom of waters. The movement of intersection animals is limited to life in and at the bottom of the water, and is very sensitive to changes in the aquatic environment, so it can be used as a bioindicator of a waters. The aim of this research to identify the types and morphology of intersecting animals in Takisung Beach, Tanah Laut Regency. The study uses descriptive survey method with observation techniques for data collection. The research sample is an intersecting animal found in the research plot. The research plot was determined by the 6 point transect, distance of 5 m between points along 1,500 m. Data were analyzed exploratively using relevant libraries. The results showed that the intersection animals found consisted of 15 types namely: Aurelia aurita, Tachypleus tridentatus, Turritella communis, Cassis tuberosa, Oliva sayana, Murex trapa, Urosalpinx cinerea, Urosalpinx perrugata, Neritina violacea, Comarmondia gracilis, Cryptospira ventricosa, Erosaria miliaris, Anadra granosa, Paphia undulata, and Solen vaginalis.